Injunctive relief in tort law - Lerch, AWF (2023)
There is a large body of contemporary and historical case law in England and Wales in which injunctions have been granted to restrain or remedy many different torts. Remarkably, however, there is a dearth of analysis of the availability of injunctive relief in tort law. This thesis seeks to impose an intelligible order on the case law concerning injunctions in tort and then consider what it tells us about tort law. The thesis begins by analysing how the injunction in aid of legal rights came to be developed as a remedy by the Court of Chancery. It then clarifies the formal distinctions between the different types of injunction. The claim is made that four types of injunction are awarded to restrain or remedy torts: prohibitory, desisting mandatory, restorative mandatory, and quia timet injunctions. The law governing the award of these injunctions in tort law is then analysed in detail. It is argued that any tort (except a cause of action generating a primary liability) can be restrained by an injunction. Furthermore, the claim is made that distinct analytical processes are employed by the courts when they decide whether to award injunctions in aid of tort law rights. Having set out the doctrinal findings as to when prohibitory, desisting mandatory, restorative mandatory, and quia timet injunctions can be granted, the thesis considers what implications the findings have for tort law more generally. The most important implication is this. The way in which tort law is expounded in textbooks and monographs, and taught in universities, needs updating. Specifically, we must not overemphasise the award of damages and neglect to highlight the importance of the injunction. The true position is that injunctive relief is as crucial as damages are to enforcing the rights that are generated by tort law.